Phytochemical Screening and Evaluation of the Antiarthritic Potentialof Ammoides pusilla Aqueous Extract on Freund's Adjuvant-Induced Rheumatoid Arthritis - Hamza Belkhodja; Khadidja Belhouala; Soumia Nehal (Tabriz University of Medical Sciences, 2021)
Background: Ammoides pusilla plant is a species of therapeutic interest which used in traditional medicines. This work aims to valorize this plant by the characterization of their bioactive components and the evaluation of the in vivo anti-inflammatory potential against a severe disease affecting the bone structure and the stability of the articular cartilage. Methods: First, the phytochemical screening of the polyphenolic extracts of A. pusilla was carried out. The second part of our study is devoted to the evaluation of the in vivo anti-inflammatory activity of the aqueous extract of A. pusilla based on the method of Freund's adjuvant-induced rheumatoid arthritis. Results: Phytochemical tests demonstrated the richness of extract with flavonoids, tannins, coumarins, anthocyanins and triterpenes. Whereas, the quantitative determination reveals that the aqueous extract of A. pusilla is the richest with bioactive components with contents of total polyphenols, flavonoids and tannins equal to 9.52 ± 0.11 mg gallic acid/g, 4.75 ± 0.05 mg quercetin/g and 8.64 ± 0.02 mg catechin/g respectively. The results of the anti-inflammatory activity showed that the aqueous infused extract of A. pusilla has an interesting antiarthritic potential on Freund's adjuvant-induced rheumatoid arthritis in mice. It is manifested by a weight gain; a normal arthritic index and biochemical parameters close to those of Diclofenac®. Conclusion: The aqueous infused extract of A. pusilla is therefore of considerable therapeutic interest as an alternative compound for the prevention of inflammation and for the improvement in bone structure.